Literary themes for students examining diverse literature to understand and compare universal themes - Hacht, Anne Marie (Literary themes for students, 2006)
"Presents a myriad of viewpoints, so that modern readers can begin to grasp the complexities of war and its impact. Such stories give voice to the individuals who fight and are fought against, who are injured, who suffer on the battlefield and at home, and who, inevitably, can no longer speak for themselves. Examines dominant and recurring subthemes in the literature of war; including survival, terrorism, leadership, and genocide."--GVRL description.